Emodin Suppresses the Migration and Invasion of Melanoma Cells - Qin, Dengke; Guo, Yu; Chen, Liang; Wang, Wanchen; Jia, Chuanlong; Zhao, Haiguang; Liu, Tianyi; Zhu, Jingjing; Zhou, Yiqun; Wang, Heng; Liu, Chi; Yuan, Mingjie (Biological & pharmaceutical bulletin, 2021)
Emodin (1,3,8-trihydroxy-6-methylanthraquinone), as an active ingredient in rhubarb roots and rhizomes, has been reported to possess various pharmacological properties including anti-tumor effects. Recent studies have confirmed that emodin inhibited cell proliferation and induced apoptosis of cancer cells. However, the inhibitory effect of emodin on the migration and invasion of melanoma cells and its underlying mechanism are still unclear. In the study, we observed the impercipient effects of emodin in B16F10 and A375 melanoma cells with strong metastatic abilities, focusing on the functions and mechanisms of migration and invasion of B16F10 and A375 melanoma cells. Cell counting kit-8 (CCK-8), colony formation test and Annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) staining tests confirmed that emodin possessed anti-proliferative and pro-apoptotic activities in B16F10 and A375 cells. The inhibitory effects on the migration and invasion of B16F10 and A375 cells were proved by wound healing assay and Transwell methods. Moreover, immunofluorescence assay approved the decrease in protein expression of matrix metalloproteinas (MMP)-2/-9 by emodin, and Western blot analyses revealed that emodin could increase the Bax/Bcl-2 ratio and inhibit the MMP-2/-9 protein expression and Wnt/β-catenin pathway in a dose-depended manner. BML-284, as an agonist of Wnt/β-catenin signaling pathway, reversed the effects of emodin on cell growth, migration and invasion in B16F10 cells. These findings may suggest that emodin treatment can be a promising therapeutic strategy for melanoma with highly metastatic abilities.